Education for pregnant women in increasing knowledge about childbirth preparation - Hartatiek Nila Karmila; Mery Susantri; Nathalya Dwi Kartika Sari; Ika Mardiyanti; Aizah Ari Setyana Yuli (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
In Indonesia, the maternal mortality rate remains high, encompassing women's health concerns such as pregnancy, childbirth, and the postpartum period. Efforts to mitigate this rate involve the provision of quality services spanning from pregnancy to contraception. Pregnant women experience physical and emotional changes that have the potential to cause anxiety, especially before giving birth. To overcome this problem, Nahdlatul Ulama University in collaboration with RSI A. Yani, Surabaya City held community empowerment activities in the form of educational seminars that focused on preparation for childbirth for pregnant women. The main aim of this seminar is to increase participants' understanding of childbirth preparation. The methodology used included online and offline seminars attended by 20 pregnant women. Analysis of the results of the pre-test and post-test questionnaires showed that there was a significant difference in participants' knowledge regarding childbirth preparation before and after the seminar, with a p-value <0.05. This community empowerment initiative is effective in increasing seminar participants' knowledge regarding childbirth preparation.Â